Maxillofacial Injuries at Ban Pong Hospital : A Review of 327 Cases - Losawatkul, Jariya (Journal of Health Science of Thailand, 2018)
A 6 year retrospective study(January 2002 - January 2008) included 327 patients, sustained maxillofacial injuries and treated at Oral & Maxillofacial surgery unit of the Surgical department, Ban Pong hospital. The results showed that most of the injuries occurred in male (78.29%) and in the 21-34year age group (31.49%). The common causes of the injury were motorcycle accident (62.08%) and personal assaults (23.85%). Drinking before injuries was reported in 35 patients (10.70%). The most common sites of injuries were symphysis of mandible (22.15%) and zygoma (20.50%). The patients had drinking or smoking behavior (58.41%). The most common treatment was closed reduction (74.21%) and the most common post operative complication was delay union (3.36%). The patients who had complications significantly had drinking or smoking behavior. (p-value<0.001, 95%CI 10.827, 24.321).